125k views
0 votes
(12y2
+ 17y - 4) + (9y2
- 13y + 3) =

User Alnet
by
4.9k points

2 Answers

1 vote

Answer:


21y^(2) +4y-1

Explanation:

Hello!


(12y^(2) +17y-4)+(9y^(2) -13y+3)

For this, we can combine like terms


12y^(2) +9y^(2)=21y^(2)

17y - 13y = 4y

-4 + 3 = -1

Combine the answers and we get


21y^(2) +4y-1

Hope this Helps!

User Rob Willis
by
6.0k points
2 votes

Answer:

21y² + 4y -1

Explanation:

(12y² + 17y - 4) + (9y² - 13y + 3) ---- remove parentheses

= 12y² + 17y - 4y + 9y² - 13y + 3

= 12y² + 9y² + 17y - 13y - 4 + 3 -----grouped like terms

= 21y² + 17y - 13y - 4 + 3

= 21y² + 4y - 4 + 3

= 21y² + 4y - 1

User Ashir Mehmood
by
4.2k points